1997
DOI: 10.3109/00207459708988479
|View full text |Cite
|
Sign up to set email alerts
|

Alpha Sleep and Information Processing, Perception of Sleep, Pain, and Arousability in Fibromyalgia

Abstract: This study examined the relationship between alpha sleep and information processing during sleep, perception of sleep, musculoskeletal pain, and arousability in patients with fibromyalgia. Patients (n = 20) were allowed to sleep undisturbed for the first 60 minutes of the study to assess amount of alpha sleep and were classified as high or low alpha generators based on quantitative analyses of alpha activity during this period. The groups were compared for performance on two memory tasks, perceptions of polyso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 21 publications
3
33
0
5
Order By: Relevance
“…Participants' descriptions of experiencing nighttime awakenings and restless sleep are consistent with previous research using objective measures of sleep [21,22]. Many participants described a pattern of sleep consisting of several blocks of sleep lasting 2-3 h during the night with periods of wakefulness in between.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Participants' descriptions of experiencing nighttime awakenings and restless sleep are consistent with previous research using objective measures of sleep [21,22]. Many participants described a pattern of sleep consisting of several blocks of sleep lasting 2-3 h during the night with periods of wakefulness in between.…”
Section: Discussionsupporting
confidence: 74%
“…People with FMS are more easily awoken [21] and compared to healthy controls have higher levels of physical activity during the night [22,23]. A longitudinal study exploring sleep and pain in patients with FMS over the course of 1 year, found that poor sleep quality at baseline was predictive of pain and sleep quality at 1 year, but baseline pain did not significantly predict sleep quality at 1 year [24].…”
Section: Introductionmentioning
confidence: 99%
“…In 20-30% of all cases, polysomnographically (PSG) defined sleep was rated as awake [3,5,29,31]. Mismatches between measured and rated state were more frequent when subjects were aroused from NREM, compared to REM sleep [26]. While most studies with intra-night awakenings were performed in normal sleeping subjects, Borkovec et al [6] and Mercer et al [23] used the technique to study sleep/wake perception in patients with insomnia.…”
Section: Introductionmentioning
confidence: 99%
“…For some, poor sleep becomes a central issue in the course of FMS and poor sleep is inextricably linked with the experience of pain [7,8,9,10]. This association appears to be bi-directional with poor sleep linked to increased reporting of pain, and increased pain linked to poor sleep [8].…”
mentioning
confidence: 99%
“…There is also evidence of possible biological factors, such as, abnormalities in the sleep physiology of people with FMS. For example, a number of studies using polysomnography monitoring have revealed that people with FMS have increased stage 1 light sleep [23] and less (Stage 4) slow wave sleep [24,25] and are more easily awoken than controls [26]. Further, it has also been proposed that people with FMS are more likely to experience an increase in alpha waves which are associated with wakefulness, during sleep (known as the alpha-delta complex), although the results are inconsistent, and the alpha-delta complex does not appear to be specific to people with FMS [27].…”
mentioning
confidence: 99%